Harmonization or Harmony, Al-Kindi, Philosophy and Religion - Angraini, Dwi Ayu (Journal of Islamic Thought and Philosophy, 2023)
This study will explain the thoughts of Al-Kindi as a Muslim philosopher figure who harmonizes thoughts between philosophy and the Islamic religion. This discussion about the harmonization between philosophy and religion begins with doubts about what is the characteristic of philosophy that is at odds with religious beliefs. The literature study approach is carried out by examining the topic of the problem in more depth according to the references found. By using this method, the writer will find as much written information as possible from the literature related to the topic of the problem for systematic identification of the theory. After conducting research using the library study method, the results of answers to the topic of the problem were found, namely through references from journals and in order to find the background of Al-Kindi's thoughts regarding the harmonization of the relationship between philosophy and Islam.